2017
DOI: 10.1080/19491034.2017.1337621
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale invaginations of the nuclear envelope: Shedding new light on wormholes with elusive function

Abstract: Recent advances in fluorescence microscopy have opened up new possibilities to investigate chromosomal and nuclear 3D organization on the nanoscale. We here discuss their potential for elucidating topographical details of the nuclear lamina. Single molecule localization microscopy (SMLM) in combination with immunostainings of lamina proteins readily reveals tube-like invaginations with a diameter of 100-500 nm. Although these invaginations have been established as a frequent and general feature of interphase n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 65 publications
(100 reference statements)
1
28
0
Order By: Relevance
“…These nanoscale invaginations, commonly referred to as type II nucleoplasmic reticulum (type II NR), [28] are thought to improve access to the nuclear interior, which is typically rich in active genes. [31] Interestingly, volumetric reconstructions revealed that the myotubes frequently exhibited deep inward invaginations in the form of type II NR (13 ± 4 per nucleus section), to a significantly greater level than was observed for myoblasts (3 ± 2) (Figure 4c,d). We next investigated whether NPCs were relocated to sites of nuclear invaginations by quantifying the percentage of NPCs localized at sites of type II NR.…”
mentioning
confidence: 93%
See 3 more Smart Citations
“…These nanoscale invaginations, commonly referred to as type II nucleoplasmic reticulum (type II NR), [28] are thought to improve access to the nuclear interior, which is typically rich in active genes. [31] Interestingly, volumetric reconstructions revealed that the myotubes frequently exhibited deep inward invaginations in the form of type II NR (13 ± 4 per nucleus section), to a significantly greater level than was observed for myoblasts (3 ± 2) (Figure 4c,d). We next investigated whether NPCs were relocated to sites of nuclear invaginations by quantifying the percentage of NPCs localized at sites of type II NR.…”
mentioning
confidence: 93%
“…Mater. 2019, 31,1900488 nuclei remained unaltered (Figure 3c,d). We also counted the number of H3K9me3 immunolabels in each group, measuring a 1.4-fold increase for the nuclei of cells cultured on microgrooves compared to those grown on flat substrates (Figure 3e).…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…Tubular invaginations of the nuclear envelope, such as those we describe here, have been observed before in a wide range of cell types and are particularly prominent in dividing cells and cancer tissue 83 . While the mechanistic relevance of these protrusions remains unclear, they have been associated with DNA repair 84 and mRNA transport 85 . These invaginations are not an exclusive feature of patient C9orf72 neurons, nor do they represent an in vitro artifact.…”
Section: Discussionmentioning
confidence: 99%